2020
DOI: 10.3390/su12208705
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable Illumination for Baroque Paintings with Historical Context Considerations

Abstract: The topic of museum illumination and conservation has been richly developed in recent years to take steps toward a zero-energy building concept. Most artworks preserved in museums’ expositions were designed for specifically defined light contexts, wherein daylight and seasonal changes were part of the artistic effect, an issue which has received little scholarly attention. From this premise, this paper aims to prove that defining the original illuminative context of artworks is required for a sustainable conse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…The Special Issue, entitled "The Future of Interior Lighting Is Here", addressed several subjects on interior lighting such as architectural lighting, daylighting, Human Centric Lighting (HCL), the impact on human health, lighting design, sustainability, and social impact and wellbeing. A total number of eleven articles, ten research papers [24][25][26][27][28][29][30][31][32][33] and one review paper [34], were published. In terms of the geographical distribution of the affiliations of the 34 contributing authors, contributions originated from ten countries, including Austria, Denmark, France, Germany, Korea, Slovakia, Spain, Sweden, Tunisia, and UK.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The Special Issue, entitled "The Future of Interior Lighting Is Here", addressed several subjects on interior lighting such as architectural lighting, daylighting, Human Centric Lighting (HCL), the impact on human health, lighting design, sustainability, and social impact and wellbeing. A total number of eleven articles, ten research papers [24][25][26][27][28][29][30][31][32][33] and one review paper [34], were published. In terms of the geographical distribution of the affiliations of the 34 contributing authors, contributions originated from ten countries, including Austria, Denmark, France, Germany, Korea, Slovakia, Spain, Sweden, Tunisia, and UK.…”
Section: Methodsmentioning
confidence: 99%
“…Luengo [31] states that a definition of the original lighting conditions is required for a sustainable conservation, ultimate interpretation, and perception of artworks. For this reason, 17th and 18th century churches from Americas, Asia, and Europe were selected and examined with modern conservation frameworks for artworks.…”
Section: Sustainabilitymentioning
confidence: 99%
“…In 2016 a study by Mayorga Pinilla et al reported an advanced daylight evaluation on the cloister of Santa Maria El Paular in Spain [32] and suggested a method using the assessment of Global Risk Factor for understanding the daylight action. In the most recent study, Luengo analyzed the issues of sustainable illumination of painting collections and reported that lighting in museum buildings should be "the result of scientific studies, both general and specific for each piece" [33].…”
Section: Lighting In Museum and Exhibition Spacesmentioning
confidence: 99%
“…Computer simulation of floodlighting is now the basic tool for any designer of such installations [1][2][3]. On its basis, the design is analysed in terms of lighting features [4,5], energy [6], and impact on the environment [7][8][9][10], and, as far as outdoor objects are concerned, its impact on the natural environment is also investigated [11][12][13]. A lighting designer has various tools and methods that are constantly improved in terms of the IT solutions [14].…”
Section: Introductionmentioning
confidence: 99%